Clinical Course and Complications of Gestational Diabetes: Approaches to Prevention and Management (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In recent years, the increasing prevalence of diabetes and its growing adverse impact on maternal and fetal health have made its management during pregnancy increasingly important. During pregnancy, attention should be given to insulin resistance and the adverse effects observed in diabetic pregnancies. Management is mainly understood as lifestyle modification and pharmacological treatment in pregnant women In patients belonging to high-risk groups, early diagnosis and early treatment are crucial factors in achieving positive outcomes.Gestational diabetes mellitus has been regarded as a medical complication of pregnancy, and it has been associated with an increased risk of developing type 2 diabetes in the mother in the future.